Factors Affecting the Job Performance of IT Professionals in Malaysian Public Universities - Mahani, Huja Husin (-, 2024)
This study investigates how organizational behavior factors at various levels, organizational, group, and individual, impact the job performance of IT professionals in Malaysian public universities. Specifically, it aims to understand the relationships between factors such as effective leadership, organizational culture, leader-member exchange (LMX), organizational commitment, emotional intelligence, and both task and contextual performance. Employing a quantitative approach, Partial Least Squares Structural Equation Modeling (PLS-SEM) reflective model was utilized to analyze the data gathered from surveys administered to IT professionals in Malaysian public universities. Contrary to expectations, our findings did not support a significant positive relationship between effective leadership, organizational culture, LMX, and organizational commitment with both task and contextual performance. However, we found a significant positive relationship between emotional intelligence and both task and contextual performance, highlighting the critical role of individual-level factors in IT professional job performance. The outcomes of this study underscore the necessity for interventions aimed at enhancing the influence of effective leadership, organizational culture, LMX, and organizational commitment on the job performance of IT professionals. Management initiatives should prioritize interventions at the organizational and group levels to optimize the job performance of IT professionals within Malaysian public universities.